Comparison of the Effect of Topical Acidulated Phosphate Fluoride Application on Surface Roughness of Two Fissure Sealants and One Flowable Composite - Leila Pishevar; Romina Mazaheri; Neda Farahmand
Introduction: fluoride application and fissure sealant therapy have an important cariostatic effect in pediatric dentistry. Investigations are indicative for effects of topical fluoride specially APF (Acidulated Phosphate Fluoride) gel on the restorative materials. The purpose of this study was to assess the effect of repeated application of APF (1. 23%) gel on the surface roughness of two fissure sealants and one flowable composite. Materials & Methods: In this experimental study, 81 specimens of two fissure sealants and one flowable composite were prepared, using special polymer mold in three groups of 27 including: unfilled resin sealant (Fissurite F, Voco), filled resin sealant (Fissurit FX, Voco) and one flowable composite (Arabesk Flow, Voco). Then, these three groups were divided into three sub groups of 9 as follows: Group 1, 4, 7 (control): No treatment. Group 2, 5, 8: Single application of APF gel. Group 3, 6, 9: Six times application of APF gel. The APF gel was applied on the surface of specimens each time for 4 minutes. Then, the specimens were stored in the distilled water. Finally, the surface roughness of the sealants was measured by Profilometer. The statistical analysis was performed by 2-Way ANOVA & One-Way ANOVA. Results: The results of the study showed a significant statistical different between the surface roughness according to the type of material (P<0.001). Unfilled fissure sealant, showed maximum surface roughness and flowable composite showed minimum surface roughness. Also, the frequency of APF gel application (once or many times), had no effect on the average surface roughness of the materials (P>0.05). Conclusion: All three materials were resistant to the destructive effects of APF gel and no significant surface roughness was detected on them.